Green synthesis, characterization and in vitro biological studies of quercetin complexes with Zn (II) acetate and N^N Moiety - Srivastava T.; Mishra S.K.; Tiwari O.P.; Tiwari K.N.; Kumar P.; Kumar J.; Singh A.K.; Singh A.; Dwivedi A. (My University, 2025)
Green synthesis of two coordination complexes of zinc acetate with N^N moiety on quercetin, which is a flavonoid is carried out. The complexes were obtained in high yields (> 97%) by grinding methods without the involvement of any solvent. Neither catalyst nor any additives were needed to perform the reactions. It was characterized by FT-IR, UV-Vis, NMR, HRMS, and elemental analysis. Antioxidant activity was done through the DPPH method which was compared with ascorbic acid and ligand (Quercetin). The study reveals that Complex 1 (IC50 163.093µg/ml) has significant free radical scavenging activity as compared to complex 2 (IC50 258.683µg/ml). Biological activity was performed against microbes (E. coli and S. aureus). MIC value of complex 1 (15.50µg/ml E. coli, 7.18µg/ml S. aureus) was found more significant as compared to complex 2 (22.51µg/ml E. coli, 18.62µg/ml S. aureus) and quercetin. © RJPT All right reserved.